سائبر کرائمز کی مختلف اقسام کا شرعی نصوص کی روشنی میں تجزیاتی جائزہ - حافظ سمیع الله; ڈاکٹر محمد حماد لکھوی (jihat-ul-islam, 2020)
Islam is the religion of nature that guides people in every field of life. As crime and punishment is one of the areas of human life, Islam also provides full guidance about it. The nature of crime is changing with the passage of time and cybercrimes are its latest example. Those who use information technology for negative purposes are called cybercriminals and all criminal activities, committed by the computer; the Internet, cyberspace and the World Wide Web are called cybercrimes. The overall rules laid down by Islamic law in relation to crime cover every form of crime, including cybercrimes. However, there are some Shariah texts that can be specifically applied to different forms of cybercrime. This article studies the same shariah texts that can be applied to different types of cybercrimes.